Editorial: rooting ICTs in forest management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Theodore Roosevelt once said that ´to exist as a nation, to prosper as a state and to live as people, we must have trees´.